Arthur J. Goldberg New Deal liberal - Stebenne, David (Oxford University Press, 1996)
In a span of four eventful years, from 1961 to 1965, longtime union advocate and liberal stalwart Arthur J. Goldberg won appointments to three of our nation's highest government posts: Secretary of Labor, Supreme Court Justice, and U.S. Representative to the U.N. Here is the first biography of Arthur J. Goldberg, one that investigates this remarkable stretch in Goldberg's public career while offering a stimulating portrait of a man who rose from working-class roots to offices that helped define the shapes of postwar union expansion and liberal policy in the 1960s. Drawing upon a wide range of sources, ranging from sealed government papers to interviews the author conducted with Goldberg in the last nine years of his life, historian David Stebenne writes of Goldberg's youth as the son of a Chicago fruit peddler, his awakening to the pursuit of labor law, and his galvanizing role as legal counsel in the late 1930s newspaper guild strike against the Hearst Company, a triumph which brought him to the attention of the Congress of Industrial Organizations. Appointed general counsel of both the CIO and the United Steelworkers Union, Goldberg advised the merger that formed the mighty AFL-CIO, while leading the fight to expel the Brotherhood of Teamsters and championing the interests of American workers in Washington. At once the biography of a leading liberal and a study of liberalism since FDR, Arthur J. Goldberg: New Deal Liberal will interest anyone concerned with social reform, Supreme Court activism, and labor history in the postwar era.